TREATMENT METHODS FOR EPITHELIAL COCCYGEAL PASSAGE (World Bulletin of Public Health, 2022)
Epithelial coccygeal passage is a congenital widespread condition and accounts for 1-2% of all surgical pathology. The incidence predominates in persons with increased hairiness, and is rare in persons of non-gracial race. Patients with persistent or recurrent purulent fistulas of the sacro-copal region are sometimes encountered among coloproctologist patients. This passage is a congenital skin anomaly associated with incomplete reduction of the muscular and connective structures of the caudal region - the epitheliococcipital passage. The surgical tactics for the treatment of epithelial-dorsal passage are practically unified. Individual approach to the choice of surgery depending on the topographic features of the coccygeal region along with application of a complex of measures for the prevention of complications during follow-up treatment make it possible to achieve good results of recovery.